If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5x + 12 = 2x + -10 Reorder the terms: 12 + 5x = 2x + -10 Reorder the terms: 12 + 5x = -10 + 2x Solving 12 + 5x = -10 + 2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. 12 + 5x + -2x = -10 + 2x + -2x Combine like terms: 5x + -2x = 3x 12 + 3x = -10 + 2x + -2x Combine like terms: 2x + -2x = 0 12 + 3x = -10 + 0 12 + 3x = -10 Add '-12' to each side of the equation. 12 + -12 + 3x = -10 + -12 Combine like terms: 12 + -12 = 0 0 + 3x = -10 + -12 3x = -10 + -12 Combine like terms: -10 + -12 = -22 3x = -22 Divide each side by '3'. x = -7.333333333 Simplifying x = -7.333333333
| 36-3x=6x+22 | | 10x+9/24=-7/24 | | 8+5x=4x+9 | | x^2=10-3(4-x) | | 4(2x-3)=4 | | 8x^2-4x-18=0 | | 3(7+x)=2x+21 | | 11x=26 | | 187=2.8t+0.5(-.0209625668)t^2 | | -2(10x+3)= | | 8x=3.5 | | (5x+2)+(x+3)= | | -8(2x+6)-(x+7)= | | 6(n-3)+2=2n+4(n-1) | | 29r=3(r^2+4) | | 12x-9x=15 | | 5x-1=-7 | | 3x^4-243=0 | | x(5x-2)=-3 | | x(5x-2)=3 | | 5x+6=23 | | 3x=2x+25 | | 3.3x=2.2x+5.5 | | x/(-2)=7 | | -8t=34 | | (c^3+2c^2d+cd^2)=0 | | X-8=40 | | 13-x=-3 | | 5-4x+5x=6x-12 | | z+1=-17 | | 4x^2+2x+7=0 | | 0.3x+0.4(10)=0.2(x+20) |